Long-term outcomes of adolescents and young adults identified by metabolic newborn screening - Mütze, Ulrike; Stengel, Julia; Gleich, Florian; Keßler, Svenja; Grünert, Sarah C.; Thimm, Eva; Hennermann, Julia B.; Freisinger, Peter; Krämer, Johannes; Schnabel-Besson, Elena; Mengler, Katharina; Shtylla, Alboren; et al. (Pediatrics, 2025)
Although newborn screening (NBS) programs were expanded with the implementation of tandem mass spectrometry in the late 1990s, the impact on long-term clinical and cognitive outcomes of adolescents and young adults with inherited metabolic diseases (IMDs) has remained fairly unknown for most IMDs.A prospective, multicenter, observational study is performed in Southwest Germany (NGS2025, DRKS-ID: DRKS00013329). For systematic follow-up from preschool up to adulthood, individuals with IMDs identified by NBS between 1999 and 2014 were included.In total, 257 (124 boys, 133 girls) screened individuals with at least 1 study visit in adolescence were followed until median age of 13.7 years. During the observation period, most did not develop permanent disease-specific signs (70.1%) or metabolic decompensations (55.2% of those at risk), had normal cognitive outcome (81.4%; IQ mean [SD], 98 [15]), and attended regular primary (91.2%) and secondary schools (90.8%). Nonetheless, NBS and early start of treatment did not prevent metabolic decompensations in 69 (44.8%) individuals at risk, and in 33 of them, metabolic decompensation occurred already before the NBS result was available. Permanent disease-specific symptoms were more frequently observed in patients experiencing metabolic decompensations compared with those without decompensations (75% vs 12.8%). Reliable therapy adherence was associated with better long-term outcome.NBS for IMDs is a highly successful program of secondary prevention for most early-diagnosed and early-treated individuals with an IMD, allowing the start in an independent life; however, therapeutic effectiveness and quality remain a relevant limitation in some diseases.
Online verfügbar: 19. März 2025
Gesehen am 28.01.2026